THE IMPLEMENTATION OF PUBLIC SECTOR ACCOUNTING ON FRAUD - Padri Achyarsyah; Muhammad Nur; Erwin Indriyanto; Kumba Digdowiseiso (CV. Radja Publika, 2023)
Transparency, people-centeredness, and accountability in financial management are key indicators of good governance. Nevertheless, in practice, the effective implementation of good governance is still lacking. In Indonesia, the occurrence of fraud is extensive, primarily characterized by instances of corruption within both the government sector and non-governmental organizations. An effective approach to address this issue is by implementing public sector accounting. Nevertheless, in light of socio-political transformations and technological upheavals, it is imperative to conduct a more comprehensive investigation into the significance of public sector accounting in relation to fraud. Therefore, this research endeavors to assess the influence of implementing public sector accounting on instances of fraud. The employed approach is a systematic literature review, with the collection strategy based on the PICOC method. The research methodology comprises several steps, namely problem identification, keyword determination, article exploration, scientific article selection, and qualitative descriptive analysis. The research findings indicate that the majority of the literature demonstrates a positive correlation between the adoption of public sector accounting and the reduction of fraudulent activities. Implementing effective governance and supervision in financial management can enhance the performance of this role. Such actions are crucial to optimize the role of public sector accounting in minimizing the potential for fraudulent activities.